Effect of SO2 Poisoning on the Electrochemical Activity of La0.6Sr0.4Co0.2Fe0.8O3-δ Cathodes of Solid Oxide Fuel Cells. Issue 6 (17th March 2017) - Wang, Cheng Cheng; He, Shuai; Chen, Kongfa; Rowles, Matthew R.; Darvish, Shadi; Zhong, Yu; Jiang, San Ping
Abstract : The effect of sulfur deposition and poisoning on the electrochemical activity of La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathode of solid oxide fuel cells (SOFCs) for the O2 reduction reaction is studied under accelerated experimental conditions. EDS, FIB-STEM and XRD analysis clearly show the sulfur deposition occurs on the surface as well as in the bulk of the electrode, forming SrSO4, CoFe2 O4 and La2 (SO4 )3 . The sulfur deposition is random and the intensity of sulfur deposition increases with the decrease in operation temperatures. This is consistent with the significantly high poisoning effect of SO2 in air on the electrocatalytic activity of LSCF electrodes for oxygen reduction reaction at low temperatures. After polarization at 200 mAcm −2 and 600°C for 20 h in 10 ppm SO2 -containing air, electrode polarization potential, ECathode increased from 750 mV to ∼2500 mV, an increase of 1750 mV, substantially higher than 135 and 48 mV for the reaction at 700 and 800°C. Sulfur deposition causes the increase of electrode polarization as well as ohmic resistances of LSCF cathodes for the O2 reduction reaction. Moreover, sulfur deposition and poisoning on the LSCF cathodes is not reversible and the irreversibility of sulfur poisoning increases with the decrease of temperature. Computational calculation indicates that the interaction between LSCF and SO2 is thermodynamically favorable, leading to complete decomposition of LSCF perovskite structure, which is in excellent agreement with the experimental results as shown in this study. Kinetically, sulfur deposition is most likely initiated by the nucleation reaction between the gaseous SO2 and segregated SrO on the surface of LSCF electrode, which accelerates depletion of Sr and leads to the decomposition of LSCF perovskite structure.